Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fpubh.2020.560389
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mental Health Problems During Virus Epidemics in the General Public, Health Care Workers and Survivors: A Rapid Review of the Evidence

Abstract: Background: The swift spread of SARS-CoV-2 provides a challenge worldwide. As a consequence of restrictive public health measures like isolation, quarantine, and community containment, the provision of mental health services is a major challenge. Evidence from past virus epidemics and the current SARS-CoV-2 outbreak indicate high prevalence rates of mental health problems (MHP) as short- and long-term consequences. However, a broader picture of MHP among different populations is still lacking. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 123 publications
1
43
0
6
Order By: Relevance
“…Another study reported that stress levels among medical staff during the pandemic were higher than usual [ 29 ]. In addition, previous studies on the mental health of the general public and healthcare workers in the COVID-19 pandemic/epidemic have been reported [ 7 , 30 , 31 ]. Our results indicate that in Japan, as in other countries, substantial mental health problems have developed among healthcare workers since implementing COVID-19 infection control measures [ 5 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that stress levels among medical staff during the pandemic were higher than usual [ 29 ]. In addition, previous studies on the mental health of the general public and healthcare workers in the COVID-19 pandemic/epidemic have been reported [ 7 , 30 , 31 ]. Our results indicate that in Japan, as in other countries, substantial mental health problems have developed among healthcare workers since implementing COVID-19 infection control measures [ 5 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Countries across the globe faced different epidemiological situations, and even those impacted in a similar manner chose to respond to the pandemic in different ways. Early and effective containment measures have decreased infection rates [ 13 ]; however, the benefits come with huge costs in terms of negative psychological outcomes [ 9 ], especially when individuals are affected by specific stressors such as greater duration of confinement, inadequate supplies, difficulty securing medical care and financial losses [ 14 ]. The home confinement of large swaths of the population for indefinite periods, differences among the stay-at-home orders issued by various jurisdictions, and conflicting messages from government and public health authorities have most likely intensified distress.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the pandemic has seriously affected economies and individual livelihoods. Previous epidemics had tremendous negative consequences on the mental health of various population groups such as health care workers and survivors of the infectious disease (Zürcher et al ., 2020 ). However, past epidemics have also negatively impacted the mental health of general populations at large (Zürcher et al ., 2020 ).…”
mentioning
confidence: 99%
“…Previous epidemics had tremendous negative consequences on the mental health of various population groups such as health care workers and survivors of the infectious disease (Zürcher et al ., 2020 ). However, past epidemics have also negatively impacted the mental health of general populations at large (Zürcher et al ., 2020 ). Therefore, during the first wave of the Coronavirus pandemic and the first phase of lockdowns, there were widespread fears concerning mental health problems beyond population groups that were directly affected by the illness (The Lancet Infectious Diseases, 2020 ).…”
mentioning
confidence: 99%